PA 19-1-0606 Effect of intimate partner violence and workplace violence on depression of female garment workers in bangladesh. (November 2018) - Parvin, Kausar; Mamun, Mahfuz Al; Gibbs, Andrew; Jewkes, Rachel; Naved, Ruchira Tabassum
Abstract : Rate of Intimate Partner Violence (IPV) is high (54%) in Bangladesh. Moreover, female garments workers reports higher rate of IPV and are vulnerable to different forms workplace violence (WPV). Experience of violence put women at increased risk of developing depressive symptoms which is related with low self-esteem, lower life satisfaction and lower productivity. However, effect of IPV and WPV on female garment workers mental health has not been studied yet in Bangladesh and the pathways through which these experience lead to development of depressive symptomatology remain unknown. This paper aims to address this gap using data from a cross sectional survey of female garment workers (n=800) conducted as baseline survey of HERrespect trial. We conducted descriptive analyses and structural equation modelling to explore the pathways. The findings shows rate of any IPV (69%) and WPV (73%) experienced or witnessed is high. Around 40% of the female workers reported depressive symptomatology. The pathways analysis shows that IPV contributed to depression through increased WPV, and work related stress; reduced life satisfaction, self-esteem, and general health. WPV was directly associated with higher depression. It also contributed to depression through work related stress, life satisfaction and general health. It also reveals that a worker's ability to mobilize resources in crisis situation, however, increased self-esteem and life satisfaction; and reduced work related stress. The rate of IPV, WPV and depressive symptomatology is high among female garment workers; these experiences of violence adversely impact their mental health through various paths. Experience of violence increased work related stress and ultimately led to development of depression, which may reduce productivity. Thus, violence incurs cost at individual, family and the garment sector levels. The findings suggest that programmes to reduce IPV and WPV and promote women's empowerment would improve women's mental health through enhanced self-esteem, life satisfaction and productivity.